Nova metodologia de medição de impedância impulsiva de aterramentos de pé-de-torre de linha de transmissão - Caio Henrique Duarte de Oliveira (2019)
This dissertation studies a new technique for measuring the transient response of grounding systems, notably impulsive impedance, using an arrangement of special conductors in the current circuit. Such conductors, called ATL (Artificial Transmission Line) are solenoids that, due to their constructive characteristics, have high surge impedance and low propagation speed. ATL units replace long cables and do not require the use of auxiliary rods in the current circuit such as in conventional measurements of electrical grounds. Thus, the aim is to drastically reduce the distances involved, facilitating and streamlining the process. First, through various experiments carried out in the laboratory, an arrangement of ATL units, called the OATL (Open-ended Artificial Transmission Line), and a measurement methodology were defined. Then, measurements were made on concentrated grounding systems (installed on low and high resistivity soils) and on tower grounding of an actual transmission line. Such measurements were made using a conventional configuration, which uses long cables and auxiliary rods in the current circuit, and a configuration with the OATL arrangement in the current circuit. The results obtained by measurements in both configurations and by means of computer simulations were analyzed through the calculation of impulsive impedance, harmonic impedance and transient impedance. The comparison of the results points to the consistency of the use of the OATL arrangement in grounding measurements, showing percentage differences between 2% and 24%, in comparison with conventional measurements.